Is the relative age effect just a European problem? A comprehensive analysis of birth date distribution and its impact on player selection at the 2023 FIFA Women’s World Cup - Benito Pérez-González; Jairo León-Quismondo; José Bonal; Iyán Iván-Baragaño; Álvaro Fernández-Luna; Pablo Burillo (PLoS ONE, 2025)
This study examines the presence and implications of the Relative Age Effect (RAE) in the 2023 FIFA Women’s World Cup, focusing on the distribution of players’ birth dates across continents and professional levels. Utilizing a sample of 735 players, a Poisson regression was conducted on the weekly birth frequency to determine the significance of the fit to a Poisson regression curve. Despite the lack of a significant RAE across the overall player population, our findings reveal notable geographical and positional variations. Specifically, European players, particularly goalkeepers and defenders, alongside the top 4 classified teams and nations with a substantial number of federation licenses, exhibit a significant RAE, suggesting a substantial impact on player selection favouring those born earlier in the year. Conversely, players from Africa, America, Asia, and Oceania do not show a significant RAE, indicating variability in its manifestation across different football environments.